Design and Implementation of H∞ Miscellaneous Information Feedback Control for Vehicle Suspension System. (20th May 2019) - Wang, Gang; Zhou, Zhijin
Abstract : In this paper, we investigate an H ∞ miscellaneous information feedback controller (HMIFC) for active suspension system stabilization. An auxiliary feedback signal is introduced in the control channel via a wireless communication network. Under this scheme, the onboard measured signal and network transmission signal are simultaneously used to improve the control performance. To handle the impact of network-induced delays, a delay-dependent stability criterion for the closed-loop system is derived based on Lyapunov theory and the linear matrix inequality (LMI) method. By considering an augmented Lyapunov–Krasovskii functional (LKF) and a relaxed integral inequality, a new existence condition of the miscellaneous feedback controller can be obtained. Compared with the traditional H ∞ controller, the designed controller can acquire better ride comfort subject to the same constraints. Finally, comparative simulation and experimental results prove the effectiveness of the presented H ∞ miscellaneous information feedback controller.